Things in Antarctica. An archaeological perspective. Issue 2 (2nd July 2020) - Senatore, Maria Ximena
ABSTRACT: The representation of Antarctica as the last wilderness overlooks not only the presence of humans but also of material things, and does not reflect the reality of contemporary Antarctica. Human-thing relationships have existed there, although largely unnoticed, since the nineteenth century. This article contributes to thinking about the genealogy of human-thing relationships in Antarctica by presenting an analysis of how the process of living with things has developed over time. Based on available historical and archaeological information, this study explores human-thing relationships during sealing and whaling activities, inside the huts of the Heroic Era of Antarctic exploration, throughout the period of the settlement of permanent scientific stations, and after the coming into force of the Madrid Protocol. From an archaeological perspective this article emphasises how things are not inert, they change, establish relations and that humans in Antarctica have often become entrapped in their relations with things. It is my hope that this introductory exploration into the topic will stimulate critical thoughts on human-thing relationships in Antarctica.